A MODEL FOR DEVELOPING AN ENVIRONMENT CONDUCIVE TO MORAL AND ETHICAL DEVELOPMENT OF BAN LUANG SCHOOL STUDENTS. NAN SECONDARY EDUCATIONAL SERVICE AREA OFFICE - Eiamudom, Suwat (Journal for Developing the Social and Community, 2024)
The purpose of this research is to create to try and to evaluate the model Develop an environment that is conducive to the development of students' morals and ethics. Ban Luang School Nan Secondary Educational Service Area Office The method for carrying out the research was 3 steps: (1) creating a model for develop an environment conducive to the development of morality student ethics by education and Analyze the content of the document. and interviewing experts and experts Drafting and verifying suitability and the possibility of a model There were 7 experts and experts. The tools used in the research were interview forms, focus group issues. and an assessment form (2) to experiment with the Develop an environment that is conducive to the development of students' morals and ethics. Ban Luang School Nan Secondary Educational Service Area Office with 13 basic education committees, 43 teachers and educational personnel, 194 students in grades 1-6 of the academic year 2020, and 194 parents of students. Develop an environment that is conducive to moral and ethical development of students at Ban Luang School, Nan Secondary Educational Service Area Office. 13 basic education committees and 38 teachers and educational personnel in the academic year 2021. The statistics used are the mean, standard deviation. and summarize information. The results showed that The model for developing an environment that conducive to moral and ethical development of Ban Luang School students. Nan Secondary Educational Service Area Office has 4 components: principles, objectives, development, environment conducive to development, morality and ethics, consisting of 4 steps: 1. Communication stage. Creating understanding 2. The practice of organizing the environment within the educational institution 3. Follow-up supervision 4. Stage of study of results from development and results from development, i.e. direct results (Output), i.e. results from the development of management environment conducive to moral development Student ethics. Outcome is discipline behavior. responsible behavior and public-minded behavior The model is appropriate and feasible at the highest level. The experimental results of the development model of the environment conducive to the development of morality. student ethics Ban Luang School Nan Secondary Educational Service Area Office found that the development of an environment conducive to moral development student ethics Ban Luang School Nan Secondary Educational Service Area Office There are 4 steps in operation and 5 main activities have been developed: (1) indoor environment development activities (2) outdoor environment development activities (3) sports field development activities (4) school development activities know Within the school and (5) activities to promote safety and prevent accidents in schools, it was found that overall practice was at a high level. and merit assessment results The ethics of students at Ban Luang School, Nan Secondary Educational Service Area Office consisted of discipline behavior. responsible behavior and behavior in public mind. It was found that overall there was practice in most level. The results of the evaluation of the development model of the environment conducive to development. student ethics Ban Luang School Nan Secondary Educational Service Area Office found that the overall possibility, suitability and usefulness were at the highest level.